Правове регулювання діяльності об'єднань співвласників багатоквартирних будинків: зарубіжний досвід - Утвенко, Володимир Валерійович (My University, 2015)
Реформування житлово-комунального господарства є одним з основних напрямків соціально-економічної політики держави та органів місцевого самоврядування в контексті реформ в Україні на шляху європейської інтеграції. Важливою складовою реформування житлово-комунального господарства України мають стати об'єднання співвласників багатоквартирних будинків, які мають стати альтернативою житлово-комунальним конторам та сприяти підвищенню якості житлово-комунальних послуг, що надаються населенню. Водночас вітчизняне законодавство не повністю регулює механізми створення та функціонування таких об'єднань, а органи місцевого самоврядування не виявляють належної ініціативи щодо правового регулювання створення об'єднань співвласників багатоквартирних будинків. Однак, як показує зарубіжний досвід, саме об'єднання співвласників багатоквартирних будинків відіграють вирішальну роль у забезпеченні населення житлово-комунальними послугами, і діяльність таких об'єднань рішуче заохочується на законодавчому рівні, зокрема органами місцевого самоврядування. Reforming the housing and communal services is one of the main directions of the socio-economic policy of the state and local self-government bodies in the context of reforms in Ukraine on the path to European integration. An important component of the reform of the housing and communal services of Ukraine should be associations of co-owners of apartment buildings, which should become an alternative to housing offices and contribute to improving the quality of housing and communal services provided to the population. At the same time, domestic legislation does not fully regulate the mechanisms for the creation and functioning of such associations, and local self-government bodies do not show due initiative in terms of legal regulation of the creation of associations of co-owners of apartment buildings. However, as foreign experience shows, it is associations of co-owners of apartment buildings that play a crucial role in providing housing and communal services to the population, and the activities of such associations are strongly encouraged at the legislative level, including by local self-government bodies.
Keywords: правове регулювання; legal regulation; житлово-комунальне господарство; housing and communal services